PROFIL KOMUNIKASI INTERPERSONAL MAHASISWA - Feida Noor Laila Isti'adah (Program Studi Bimbingan dan Konseling Universitas Muhammadiyah Tasikmalaya, 2017)
This research is held based on the fact that a few students have difficulties to express their opinion in a discussion forum. The students tend to be silent while the opportunity to ask questions has been given, the students unable to say â€œnoâ€ or to reject other studentâ€™s will, and misconceptions among peer members of discussion group may often lead to a conflict. Moreover, studentâ€™s interpersonal communication has to be improved because it has an important role in daily life, particularly on social interaction. Especially in dealing with others, especially students of the FKIP Umtas. The purpose of this study to determine the general picture of interpersonal communication students of the FKIP Umtas. Research using descriptive methods. Instruments used to describe the interpersonal communication students collected through questionnaires. Results showed generally interpersonal communication students of the FKIP Umtas Force in 2015 at the high category. That is, students of FKIP Umtas have already demonstrated the intensity of interpersonal communication that is relatively well on most aspects and indicators of student interpersonal communication.